Geotecnologias aplicadas ao estudo das nascentes na bacia do Rio Lonqueador: gestão de APPs e mapeamento interativo - Braz, Gabriel (2025)
Water plays a vital role in life and environmental sustainability, but the degradation of water springs in watersheds compromises its availability. This study used geotechnology tools, such as Geographic Information Systems (GIS) and remote sensing, to investigate the socio environmental conditions of the Lonqueador Watershed, located in southwestern Paraná between the cities of Francisco Beltrão and Marmeleiro. The research sought to validate the locations of water springs, delimit Permanent Preservation Areas (PPA) and analyze the socio environmental vulnerabilities associated with land use. The methodology included the application of interactive maps, which allow all data to be observed in an integrated and interactive way. It was found that urban expansion, combined with inadequate land use and occupation practices, is the main threat to the quality of water springs. The research also identified critical areas with greater socio-environmental vulnerability associated with the lack of basic infrastructure, such as sanitation and solid waste collection, and low income of the population. These factors amplify environmental impacts and reinforce the need for effective public policies to protect springs and ensure the hydrological balance of the watershed. The results were integrated into a GIS platform that allows continuous monitoring of springs, risk assessment and intervention planning. The study concludes that the use of geotechnologies offers a basis for sustainable management of watersheds, assisting in the recovery of degraded areas, the protection of springs and the development of strategies to mitigate the impacts of urbanization. The maps and scenarios generated serve as strategic tools for the formulation of environmental policies and for raising awareness in society about the importance of preserving water resources.